Civic Participation and Demonstrations in Portugal (2011–2012) - Silva, Célia Taborda (European Journal of Multidisciplinary Studies, 2019)
In recent years, a little over the world, emerged social protest, from the Arab Spring to the Indignados, resulting from the dissatisfaction of the citizens and fruit of the speed with which the information circulates and is shared. In Portugal, the tendency to protest was in the same direction as in Europe and the world, as demonstrated by the movements of March 12, 2011 (Scratch Generation), and of September 15, 2012 (Screw the Troika). These movements brought together thousands of people in protest against government policies and in defense of a new political, economic and social model. In several cities of the country, the Portuguese, as citizens, intervened in the public sphere and expressed themselves on issues related to them, such as the crisis, unemployment, exploitation, as persons belonging to a community. The novelty was the use of communication technologies and social networks to appear, acquire visibility, then existence, as Hannah Arendt (2005) would say. Through the use of digital communication, they ignored the traditional leaderships to call out the protests and demonstrate on the streets, causing these phenomena not to be geographically or culturally limited nor institutionally framed. The internet has brought tools that foster sharing, facilitate civic participation and collective action. Thus, at the beginning of the twenty-first century, social movements have come to play a key role in the democratic state, through the representation of the claims of different sectors of civil society, but are these manifestations indicative of a new civic consciousness?